Government Responses to COVID-19: A Comparative Analysis of Visegrad Countries - Zafer Koca (Central European Public Administration Review)
Purpose: The purpose of this study is to compare government responses and the challenges faced by public authorities in the Visegrad/V4 countries during the Covid-19 outbreak.